Wooden Houses in Irkutsk Downtown: a Burden or Unused Touristic Resources? - Chertilov, Alexei (project baikal, 2015)
The article tells about the poor condition of valuable old wooden housing in the central part of the historical settlement, the city of Irkutsk. The major part of this historical and cultural genetic pool has been ruthlessly demolished for reasons of predatory construction business in the last 25 years, being already in the list of cultural heritage. Various solutions of the problem are considered in the article.
Keywords: Irkutsk; wooden architecture; historical center; housing estate; cultural property; monuments of architecture; museum of wooden architecture; museum-tourist complex